Management of Malignant Vulval Melanoma: A Retrospective Case Series and Review of the Literature. Issue 3 (July 2020) - Platt, Sarah; Coleridge, Sarah; Hughes, Geoff; Donkers, Hannah; Wiggans, Alison; Frost, Jonathan; Rolland, Phil; Julian, Sophia; Morrison, Jo; Pawade, Joya; Patel, Amit; Newton, Claire
Abstract : Objectives: The aims of the study were to evaluate clinicopathologic features, management, and outcomes in vulval melanoma and to review the literature. Materials and Methods: Data were collected retrospectively on patients with vulval melanoma from 2001 to 2017 in 5 gynecological oncology cancer centers (Bristol, Taunton, Truro, Plymouth, and Cheltenham). SPSS software was used for univariate and multivariate statistical analysis. Disease-specific median survival was calculated using Kaplan-Meier curves. Results: Forty-four patients with vulval melanoma were included, with a median age of 71 years. Forty-three of 44 had wide local excision with full inguinal lymphadenectomy if abnormal lymph nodes. Seven patients had sentinel lymph nodes. However, 2 patients with negative sentinel lymph nodes had distant recurrences within 16 months. On univariate analysis, presence of ulceration ( p = .012), perineural invasion ( p = .03), and area of lesion ( p = .016) were associated with risk of recurrence but only presence of microsatellites ( p = .01) was associated with risk of death. There were 31 deaths (70%): 29 (94%) of 31 from melanoma and 28 (64%) of 44 recurrences: 17 local (10 groin, 7 vulval) and 9 distant. Overall median survival was 32.5 months (95% CI, 17.8–46.5 months) and median recurrence-free survival 12.6 months (95% CI, 7.7–17.4 months). Conclusions: This retrospective multicenter study highlights the high recurrence rate and poor prognosis of vulval melanoma. Lymph node surgery did not make any difference to recurrence-free survival or overall survival. The presence of microsatellites was associated with a statistically increased risk of death.